A Phytophthora capsici RXLR effector manipulates plant immunity by targeting RAB proteins and disturbing the protein trafficking pathway. (3rd October 2022) - Li, Tianli; Ai, Gan; Fu, Xiaowei; Liu, Jin; Zhu, Hai; Zhai, Ying; Pan, Weiye; Shen, Danyu; Jing, Maofeng; Xia, Ai; Dou, Daolong
Abstract: The oomycete pathogen Phytophthora capsici encodes hundreds of RXLR effectors that enter the plant cells and suppress host immunity. Only a few of these genes are conserved across different strains and species. Such core effectors might target hub genes and immune pathways in hosts. Here, we describe the functional characterization of the core P. capsici RXLR effector RXLR242. The expression of RXLR242 was up‐regulated during infection, and its ectopic expression in Nicotiana benthamiana, an experimental plant host, further promoted Phytophthora infection. RXLR242 physically interacted with a group of RAB proteins that belong to the small GTPase family and play a role in regulating transport pathways in the intracellular membrane trafficking system. In addition, RXLR242 impeded the secretion of PATHOGENESIS‐RELATED 1 (PR1) protein to the apoplast. This phenomenon resulted from the competitive binding of RXLR242 to RABE1‐7. We also found that RXLR242 interfered with the association between RABA4‐3 and its binding protein, thereby disrupting the trafficking of the membrane receptor FLAGELLIN‐SENSING 2. Thus, RXLR242 manipulates plant immunity by targeting RAB proteins and disrupting protein trafficking in the host plants. Abstract : RXLR242 from Phytophthora capsici disturbs the host protein trafficking pathway by competitively interacting with RABE1‐7 and RABA4‐3, and finally interfering with the transporting of PR1 and FLS2.